Factors influencing pediatric nurses' compliance with risk of falls prevention standards to achieve patient safety at Wonosari Hospital Special Region of Yogyakarta - Widiawati, Anita; Lienawati, Alida; Nurunniyah, Siti (Alma Ata University Press, 2024)
Background: The incidence of fall risk for inpatient pediatric patients increased from 2022 to 2023. The incident is a serious problem and has an impact on child morbidity and mortality. The incident occurred due to a lack of evaluation of nurses' compliance with efforts to prevent the risk of falls in hospitalized children. Several studies have been conducted to determine the factors that affect nurses' compliance with fall risk prevention standards, such as education, attitude, motivation, workload and work environment factors but have not been carried out systematically on all of these factors and have not been implemented specifically for pediatric nurses.Objectives: This study aims to find out what factors most affect nurses' compliance with fall risk prevention standards in hospitalized children at Wonosari Hospital.Methods: This study uses a cross sectional approach. The population is 86 respondents of nurses that holding care in pediatric rooms. Samples were taken using the total sampling technique. Compliance, knowledge, attitudes ,motivation ,workload and work environment measured by valid and reliable adoption questionnaire with calculates r > table r and Cronbach's alpha > 0.70).Results: The results show that the p value of <0.05 There is a relationship between knowledge, attitudes, motivation, workload, and work environment to comply with the prevention of the risk of falling. The most influential factor on nurses' compliance is the motivation factor, was shown to have an odds ratio value of 83.444 followed by knowledge factors (OR=58.164), attitude (OR=4.064), workload (OR=0.626), and work environment (OR=0.085).Conclusions: There is a relationship between knowledge, attitudes, motivation, workload and work environment to compliance with the risk of falling in hospitalized children. Motivation is the most influential factor in nurse compliance, It is hoped that the management of the hospital, will evaluate programs to prevent the risk of falling in hospitalized children